The Role of Ultrasound-Based Monitoring of Bladder Volume in Patients with Prostate Cancer during CyberKnife Stereotactic Radiosurgery - Dawid Bodusz; Joanna Brajczewska-Bello; Tomasz Rutkowski; Zofia Kołosza; Alexander Jorge Cortez; Magdalena Szymala-Cortez; Wojciech Leszczyński; Jerzy Wydmański (Applied Sciences, 2024)
(1) Background: For patients irradiated due to prostate cancer, monitoring of bladder volume (BV) is crucial for accuracy of radiation delivery and minimizing exposure to surrounding healthy tissues. Due to the limited imaging capabilities of the CyberKnife system, ultrasound imaging plays a vital role in the monitoring of bladder filling. (2) Methods: A study was carried out in 142 prostate cancer patients treated with the CyberKnife system. Bladder ultrasound (US) was performed before each RTH session to assess real BV (rBV). The double US assessment of rBV was performed by two independent operators or a single operator during 177 and 495 RTH sessions, respectively, giving, in total, 1344 BV assessments. (3) Results: The mean BV in the first and second US assessment was 214.7 mL and 218.1 mL, respectively, while the mean planning bladder volume (pBV) was 340.8 mL. A pBV was significantly higher than an rBV. The mean difference between the US and CT assessment of BV was the smallest in the 100–349 mL group and the largest in the group above 349 mL. The Passing–Bablok regression results confirmed the reliability of the ultrasound (US) measurements. (4) Conclusions: The introduction of US-based BV assessment in patients irradiated due to prostate cancer using CyberKnife seems to be a crucial element in controlling the reproducibility of the treatment plan and should be a standard procedure. The pBV should be within the range of 200–300 mL. The US examination prior to CT scanning for planning is recommended to ensure the optimal range of BV for CT.